Recent Referees (Journal of Political Economy, 2021)
Previous articleNext article FreeRecent RefereesFull TextPDF Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Martin AbelJerome AddaVictor AguiarCarlos Alos-FerrerPeter ArcidiaconoCristina ArellanoEnghin AtalayChristopher AveryHeski Bar-IsaacMarco BattagliniTheodore BergstromB. BernheimManudeep BhullerAdrien BilalNick BloomLuigi BocolaStephane BonhommeNina BoyarchenkoKate BundorfDavid ByrneAlexander CappelenStefano CariaScott CarrellGabriel CarrollGary CharnessDenis ChetverikovEric ChynDavid J. CooperThomas CornelissenZoe CullenBrendan DaleyGiacomo De GiorgiAureo de PaulaMelissa DellWouter DesseinMichael DicksteinDave DonaldsonOlivier DonniAlessandro DovisWioletta DziudaJanice EberlySara EllisonSeda ErtacSadegh EshaghniaJack FanningShuaizhang FengJesus Fernandez-VillaverdeBernd FitzenbergerJeremy FoxLawrence GlostenDaniel HamermeshStephen HansenRick HarbaughRachel HeathBurton HollifieldShota IchihashiHidehiko IchimuraRyota IijimaAlex ImasRuixue JiaGabriel Jimenez ZambranoJuanna JoensenJustin JohnsonBoyan JovanovicLouis KaplowAdam KaporRohan KekreJason KerwinJudd KesslerAnton KolotilinSerhiy KozakTimothy LaytonEdwin LeuvenChristian LeuzShengwu LiIlse LindenlaubAttila LindnerAriel ListoLance LochnerKatrine LokenCorinne LowJay LuDarren LubotskyRalph LuettickeAnnamaria LusardiGeorge MailathJames MalcomsonNadya MalenkoIsabela ManeliciDaniel MartinYusufcan MasatliogluGregor MatvosMichael McMahonCostas MeghirMoritz Meyer-ter-VehnAmeet MorjariaMelanie MortenIsmael MourifieJoseph MullinsPaul NiehausTerrance OdeanHessel OosterbeekJuan OrtnerAdam OsmanIgnacio Palacios-HuertaPer Pettersson-LidbomLaura PilossophLuigi PistaferriAndrea PratStephen ReddingJohn RogersEvan RoseEsteban Rossi-HansbergThomas RuchtiBernard SalanieYuval SalantManuel SantosFrank SchilbachTodd SchoellmanBradley ShapiroJoseph ShapiroRan ShorrerDan SichelEric SimsJanis SkrastinsAndrzej SkrzypaczIsaac SorkinJohannes SpinnewijnCharles SprengerMeredith StartzNicole SteckPhilipp StrackPhilip StrahanBruno StruloviciJustin SydnorJean-Marc TallonMichela TincaniChristoph TrebeschMarta Troya MartinezNick TsivanidisBertil TungoddenRaluca UrsuBas van der KlaauwRobert Van OrderShoshana VassermanFrederic VermeulenChristian vom LehnChristopher WaltersBart WilsonMatthew WiswallArlene WongDanny YaganJun YangAndy ZapechelnyukJin ZhouSeth ZimmermanPiotr Zoch Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 129, Number 6June 2021 Article DOIhttps://doi.org/10.1086/715536 Views: 457 © 2021 by The University of Chicago. All rights reserved. Crossref reports no articles citing this article.